UJI AKTIVITAS JAMU GENDONG KUDU LAOS (Morinda citrifolia L.; Alpinia galanga L.) SEBAGAI ANTIDIABETES PADA TIKUS YANG DIINDUKSI STREPTOZOTOCIN - ., Riswanda Yulianti (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Kudu laos traditional drink is a mixture of Morinda citrifolia L. fruit extract and Alpinia galanga L. rhizome. Both of the plants are known haveantidiabetic activity from in vivo data. The purpose of this study is to determinethe antidiabetic effect of kudu laos traditional drink in lowering blood glucoselevels and percent of the area damage islet of langerhans. Twenty five male wistarrat are divided into five groups: normal group (no treatment), streptozotocin groupinduced by streptozotocin dose 7 mg/200gBB, glibenklamid group induced bystreptozotocin dose 7 mg/200gBB and treated with glibenklamid suspension dose0,27 mg/200gBB, doses group 1Â and doses group 2 induced by streptozotocindose 7 mg/200gBB and treated with kudu laos traditional drink dose 1,9ml/200gBB and 3,8 ml/200gBB. All of the treatment last 28 days. After 28 daysof treatment with kudu laos traditional drink dose 1,9 ml/200gBB and 3,8ml/200gBB there is a decrease in blood glucose levels respectively 103,2 mg/dland 117,8 mg/dl and percent of the area demage islet of langerhans each of4,114% and 4,263%Â that are significantly different (P>0,05) with streptozotocingroup. The conculsion is jamu gendong kudu laos has the antidiabetic activitieswith effective dose 1,9 ml/200gBB.Keywords: Diabetic, Streptozotocin, Kudu laos traditional drink, Blood glucose levels, Damage islet of langerhans